THE TIME COURSE OF CHANGES IN BIOMARKER LEVELS AND THE ULTRASONIC SIGNS OF INFLAMMATION IN PATIENTS WITH RHEUMATOID ARTHRITIS - O. G. Alekseeva; A. A. Novikov; M. V. Severinova; A. S. Avdeeva; E. N. Aleksandrova; E. I. Luchikhina; D. E. Karateev; S. I. Glukhova; A. V. Volkov; E. L. Nasonov (Научно-практическая ревматология)
Subclinical inflammation detected by ultrasonography (USG) promotes the progression of joint injury in patients with rheumatoid arthritis (RA). Performed studies ambiguously assess the association of disease activity indices with the Doppler ultrasonic signs of synovitis and the serum concentration of cytokines in patents with RA.Subjects and methods. Thirty-eight patients with early RA, who were followed up within the framework of the REMARCA program, were examined. All the patients' therapy was started with subcutaneous methotrexate (MTX) with its rapid dose escalation up to 20–30 mg/week and assessment of the achievement of the treatment goal (low disease activity or remission) every 3 months according to the reason why a decision had been made to add biological agents to the therapy. Clinical and standard laboratory parameters with calculated disease activity indices (DAS28, CDAI, SDAI) were analyzed immediately before and 12, 24, and 48 weeks after treatment. Blood cytokine concentrations were determined by the xMAP multiplex technology before and then 12 and 24 weeks after therapy. USG of 8 joint areas of the hands and feet was undertaken prior to and then 12, 24, and 48 weeks following treatment. Gray-scale synovial hypertrophy and synovial power Doppler (PD) signals were rated for each joint area (0 to 3 scores).Results and discussion. During the drug therapy, all the patients showed improvement with a reduction in activity indices (DAS28, SDAI, CDAI; p < 0.001) and PD signals (p < 0.05). After 12 months of therapy, the ultrasonic signs of remission were found in 4 (21%) patients with clinical remission, amounting to 11% of all the patients included in the study. In a group of patients with active inflammation persisting after 48 weeks of therapy, the basal concentration of interleukin-6 (IL-6) was significantly higher than that in a group without signs of inflammation (p = 0.025). There was a trend for higher tumor necrosis factor-α (TNF-α) levels in the persistent inflammation group (p = 0.06); however, following 24 weeks, the concentration of TNF-α in the patients with persistent synovitis was significantly higher than in those without the latter (p = 0.045). The baseline level of IL-6 as a prognostic factor showed satisfactory sensitivity (71%) and specificity (67%) for a cut-off value of 46.02 pg/ml (p < 0.025). The TNF-α level of ≤51.79 pg/mg achieved after 6 months was associated with the absence of active inflammation, as evidenced by PD with 64% sensitivity and 62.5% specificity (p < 0.046). The predictive value of DAS28 following 24 weeks (3.26) was lower than that of IL-6. Thus, PD USG of hand and foot joints is a sensitive and specific method to assess RA activity. The association of the basal level of IL-6 (and TNF-α to a lesser extent) with ultrasonic changes after 48 weeks of therapy may suggest that PD USG can more accurately characterize inflammation activity than can the disease activity indices.